(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2026)
This study aimed to identify the professional and ethical standards that govern the performance of Jordanian media professionals working in radio and television newsrooms. The study adopted a descriptive survey research design, employing a field survey method. A sample of 100 media professionals and journalists was selected using a simple random quota sampling technique from among those working in newsrooms at the Jordan Radio and Television Corporation, Al-Mamlaka TV, and Roya TV, whose total population consisted of 180 media professionals. The findings revealed that good relationships between senior management and media professionals working in newsrooms positively affect their professional performance, ranking first among the effects of the media work environment on journalists. Regarding the impact of editorial policy on professional performance, the results showed that broadcasting content is limited to what aligns with the channel’s editorial policy. In addition, the study indicated that the lack of adequate laws and legislation to protect freedom of media work negatively affects the professional performance of media professionals working in newsrooms. The study further demonstrated that the most prominent impact of professional values and ethics on newsroom performance is ensuring accuracy when addressing various topics and issues. Finally, the results showed that the proportion of female media professionals and journalists working in newsrooms remains relatively low compared to their male counterparts.